Effect of Scallop Powder Addition on MICP Treatment of Amorphous Peat - Gowthaman, Sivakumar; Chen, Meiqi; Nakashima, Kazunori; Kawasaki, Satoru (Frontiers in Environmental Science, 2021)
Peat is one of the most challenging and problematic soils in the fields of Geotechnical and Environmental engineering. The most critical problems related to peat soil are extremely low strength and high compressibility, resulting in poor inhabitancy and infrastructural developments in their vicinity. As yet, peat soils were stabilized using Portland cement; however, the production of Portland cement causes significant emission of greenhouse gases which is not environmentally desirable. MICP (microbial induced carbonate precipitation) is an innovative technique for improving the mechanical properties of soil through potentially environmentally friendly processes. This article presents the laboratory work carried out with the aim of investigating the viability and effect of scallop shell powder (SSP) on enhancing the mechanical properties of MICP treated amorphous peat. The hypothesis was that the distribution of SSP (as-derived calcite particles) would (i) provide more nucleation sites to the precipitates, (ii) increase the connectivity of MICP bridges to facilitate mineral skeleton to amorphous peat and accompanying by an increase in its compressive strength. Specimens were treated at varying combinations of SSP and MICP reagents, and the improvement was comprehensively assessed through series unconfined compression tests and supported by microscale and chemical analysis such as scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) analysis and X-ray diffraction (XRD) analysis. The outcomes showed that incorporating SSP in MICP treatment would be a promising approach to treat amorphous peat soils. The proposed approach could improve the unconfined compressive strength (UCS) by over 200% after 7 days curing period, while the conventional MICP could not exhibit any significant improvements.